Influence of the digital economy on women's empowerment in rural tourism destinations: A case study of Yudong Village in Quzhou City, Zhejiang Province - WANG Menghan, SU Mingming, WANG Yanan, DONG Hangyu, ZHANG Mengzhen (Ziyuan Kexue)
[Objective] With the rapid development of the digital economy, rural areas are experiencing new growth opportunities, particularly in providing more employment and entrepreneurship opportunities for rural women. Therefore, it is significant to explore the impact of the digital economy on women's empowerment in rural tourism destinations. [Methods] In this study, a six-dimensional analysis framework for promoting women's empowerment through the digital economy was constructed. Yudong Village in Quzhou City, Zhejiang Province was selected as a case study site. Qualitative research methods, such as participatory observation and semi-structured interviews, were applied to explore the empowerment paths of rural women in the economic, political, social, psychological, educational, and technological dimensions promoted by the digital economy. [Results] The results are as follows: (1) Based on residents' perceptions, this study analyzed the influence of the digital economy on women's empowerment in six dimensions. Economic and technological empowerment were considered the core dimensions, followed by social and educational dimensions, while the impact on political empowerment was not significant. (2) Personal factors such as women's age and education level, external factors such as the way and degree of participation in the tourism industry, family support atmosphere, and community development environment all have a significant impact on the level of women's empowerment. (3) The digital economy significantly affected women's empowerment through various forms such as the rural brain and social media. The level of empowerment was affected by individual women and external environmental factors, and presented a gradual characteristic. [Conclusion] To further enhance the level of women's empowerment and promote the sustainable development of ruraltourism, the government should leverage the digital technology advantages of enterprises and improve rural women's digital participation capabilities, while promoting the construction of digital village.